2011
DOI: 10.1179/174329009x424528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of microstructure and compressive behaviours of PM TiAl alloy prepared by HIP and pseudo‐HIP technology

Abstract: The present work discusses conditions of comparable microstructure and compressive behaviours of powder metallurgy (PM) Ti-46Al-(Cr,Nb,W,B) (at.-%) alloy prepared by hot isostatic pressing (HIP) and pseudo-HIP technology respectively. A PM route based on pseudo-HIP of alloy powder prepared by plasma rotating electrode process was used for the rapid fabrication of high quality TiAl alloys. The pseudo-hipped alloy shows a fine grained microstructure which is significantly finer than that of the hipped alloy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Table 3 shows the hardness variation of TiAl matrix composites with different carbon contents. It can be seen from Table 3 that the hardness of composites was enhanced with the low addition of C. Zhang et al [76] found that the hardness of the Ti-47Al-4Nb-2Cr-(0-0.8)C alloy increased by 38.9%, from 2.85 GPa to 3.96 GPa, with the increased carbon content.…”
Section: Hardnessmentioning
confidence: 98%
“…Table 3 shows the hardness variation of TiAl matrix composites with different carbon contents. It can be seen from Table 3 that the hardness of composites was enhanced with the low addition of C. Zhang et al [76] found that the hardness of the Ti-47Al-4Nb-2Cr-(0-0.8)C alloy increased by 38.9%, from 2.85 GPa to 3.96 GPa, with the increased carbon content.…”
Section: Hardnessmentioning
confidence: 98%
“…The lamellar structure began to appear in local regions as the HIP temperature increased to 1150 • C, as shown in Figure 11c. In the lamellar structure, the lamellar α 2 phase reduces the interstitial atom concentration in γ phase, resulting in the weakened ability of P-N stress pinning dislocations, and the enhanced deformation ability of γ phase, reducing the hardness of the microstructure, so the hardness decreases after the lamellar structure appears [42]. With an increase in the HIP temperature, the densification increases, which is helpful for increasing hardness.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In addition, the tensile strength of the 4# HIP billet was 444.7 MPa, which was higher than that of as-cast (385.9 MPa). This was mainly because of the poor mechanical properties of the cast alloy due to its coarse structure and severe constitution segregation [42]. Meanwhile, with the increase in the HIP temperature, the compressive strength and bending strength decreased gradually, and the compressive strain first decreased and then increased.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Oxygen contamination in uences the mechanical properties of titanium alloys. Small increase in oxygen content in HIP prepared samples can lead to a signi cant decrease in elongation 21) . Therefore, to ensure that the titanium alloys have better mechanical properties, the oxygen increment should be strictly controlled during powder preparation.…”
Section: The Relationship Between Rotating Speed and Particle Size Cmentioning
confidence: 99%